Infrastructure for model-based production scheduling. (4th October 2010) - Jain, Sanjay; Monch, Lars; Jahnig, Thomas; Lendermann, Peter
A large body of literature exists on algorithms and approaches for model-based production scheduling; however, very few of these developments have made it to the production shop floor. One of the major obstacles for implementation of model-based scheduling is the lack of required infrastructure. Very limited literature exists on the required infrastructure contributing to continued existence of the obstacle. This paper discusses the required infrastructure for supporting implementation of model-based production scheduling software. The focus of the paper is on tangible factors though the human factors are briefly discussed. Five major issues are identified and rank ordered based on their criticality. The relevance of each of the major issues is considered with respect to two major aspects of model-based production scheduling – schedule evaluation and periodic and real time schedule generation. Examples of real life implementation experience are provided in support of the identified issues.